2021
DOI: 10.3390/min11020229
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Up of Decanter Centrifuges for the Particle Separation and Mechanical Dewatering in the Minerals Processing Industry by Means of a Numerical Process Model

Abstract: Decanter centrifuges are frequently used for thickening, dewatering, classification, or degritting in the mining industry and various other sectors. Their use in an industrial process chain requires a sufficiently accurate prediction of the product and the machine behaviour. For this purpose, experiments on a smaller pilot-scale are carried out for scale-up of a decanter centrifuge, which is usually a major challenge. Predicting the process behaviour of decanter centrifuges from laboratory tests is rather diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…For both pool depths, the white box model follows the general trend that the solids mass fraction decreases with increasing rotational speed and the two white box models are basically equivalent, as the white box model is not sensitive enough to this difference in the pool depth. A more detailed discussion has been provided in previous publications with validation tests [12,14]. The experimental results reveal that for the same rotational speed, the solids mass fraction is higher at the smaller pool depth.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…For both pool depths, the white box model follows the general trend that the solids mass fraction decreases with increasing rotational speed and the two white box models are basically equivalent, as the white box model is not sensitive enough to this difference in the pool depth. A more detailed discussion has been provided in previous publications with validation tests [12,14]. The experimental results reveal that for the same rotational speed, the solids mass fraction is higher at the smaller pool depth.…”
Section: Resultsmentioning
confidence: 83%
“…However, correction does not mean that the simulation results are unreliable and have to be corrected in all cases. In previous works [12][13][14] it was demonstrated that the method is indeed valid. Here, an enhancement must be created to consider effects that have not been modelled or to cover cases where no physical equations are known.…”
Section: Methodsmentioning
confidence: 87%
See 3 more Smart Citations